Automatic test pattern generation for functional register-transfer level circuits using assignment decision diagrams. - Ghosh, I. (IEEE Transactions on computer-aided design of integrated circuits and systems)
In this paper, we present an algorithm for generating test patterns automatically from functional register-transfer level (RTL) circuits that target detection of stuck-at faults in the circuit at the logic level. In order to do this, we utilize a data structure named assignment decision diagram that has been proposed previously in the field of high-level synthesis. With the advent of RTL synthesis tools, functional RTL designs are now widely used in the industry to cut design turn around time. This paper addresses the problem of test pattern generation directly at this level due to a number of advantages inherent at the RTL. Since the number of primitive elements at the RTL is usually less than the logic level, the problem size is reduced leading to a reduction in the test-generation time over logic-level automatic test pattern generation (ATPG). Also, a reduction in the number of backtracks can lead to improved fault coverage and reduced test application time over logic-level techniques. The test patterns thus generated can also be used to perform RTL-RTL and RTL-logic validation. The algorithm is very versatile and can tackle almost any type of single-clock design, although performance varies according to the design style. It gracefully degrades to an inefficient logic-level ATPG algorithm if it is applied to a logic-level circuit. Experimental results demonstrate that over 1000 times reduction in test-generation time can be achieved by this algorithm on certain types of RTL circuits without any compromise in fault coverage